Development of Interactive Monopoly Games on the Pillars of Islam and Pillars of Faith - Al Zahra, Farahdiba; Safitri, Nikmah; Mandeng, Jefry; Putranta, Himawan (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
The game of Monopoly has proven to be an effective and engaging learning tool for children. In the context of Islamic Religious Education (PAI) for first-grade elementary school students, developing a modified version of the Monopoly game focusing on the concepts of the Five Pillars of Islam and the Six Pillars of Faith could be an innovative and enjoyable way to introduce these concepts to students. The game board will be designed with various locations representing the Five Pillars of Islam and the Six Pillars of Faith, the Quran. Each location will present questions or tasks designed to reinforce students' understanding of these concepts. Players will choose characters associated with Islamic figures and move around the board, answering questions, and performing tasks related to the Five Pillars of Islam and the Six Pillars of Faith. Through active interaction with the learning material, it is hoped that students can strengthen their understanding of the basic principles of Islam. The goal of this game is to stimulate students' interest in learning PAI, introduce the concepts of the Five Pillars of Islam and the Six Pillars of Faith in a fun way, and build their understanding of the values of Islam. Thus, this Monopoly game is expected to be an effective tool in helping first-grade elementary school students understand the basic concepts of Islam while enhancing their engagement and interest in learning PAI.